2014
DOI: 10.1007/978-3-319-07227-2_74
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Culture Differences on Cloud Computing Adoption

Abstract: Abstract. To cut cost, while increasing competitiveness, more and more small and medium-sized enterprises (SMEs) are considering cloud computing technology for supporting their business processes. However, initial cost, possible long term cost, security, accessibility and transformation issues are concerned by the organizations. By adopting LEADing Practices and Hofstede [16] national culture dimensions, this study provides substantive conclusions about the transformation effects of national culture dimensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Culture has been considered something that affects the reason for and rate of ICT, including cloud computing adoption. It is suggested that culture can impede the implementation efforts because of the differences in the way ICTs are interpreted and given meaning [45,46]. In a country like Yemen, with a strong tribal culture, it is highly probable that people will adopt the views of their surrounding groups, and the same applies to institutions whose employees are no more autonomous [23].…”
Section: The Research Modelmentioning
confidence: 99%
“…Culture has been considered something that affects the reason for and rate of ICT, including cloud computing adoption. It is suggested that culture can impede the implementation efforts because of the differences in the way ICTs are interpreted and given meaning [45,46]. In a country like Yemen, with a strong tribal culture, it is highly probable that people will adopt the views of their surrounding groups, and the same applies to institutions whose employees are no more autonomous [23].…”
Section: The Research Modelmentioning
confidence: 99%
“…It is particularly relevant to adoption of new IT (Zhao et al, 2014). Flexibility involves the ability of an organization to rapidly and easily adapt to up-to-date services to support business processes (Mell & Grance, 2011;McCabe & Hancock, 2009).…”
Section: Cloud Flexibilitymentioning
confidence: 99%
“…Thus, maintaining successful business opportunities by SMEs is critical to the growth of national economies in developing countries, includingJordan.Meanwhile,adoptinginnovativetechnologies,forexample,cloudERPsystems, iscrucialtothesustainabilityofSMEs (Chanetal.,2019).Therefore,itisimportanttoexploreand examinethefactorsthatallowSMEstobringinnovativetechnologyintobestpracticeandutilizeits fullpotentials.Thatisbeingsaid,themostcriticalfactorinthesuccessofEISimplementationin SMEsisthehumanfactor (Parthasarathy,2013).Thatis,theacceptanceofend-usersatalllevelsto adaptEIStoperformtheirtasks (Kim&Kankanhalli,2009). WhentheliteratureabouttheintentiontoadoptcloudERPsystemsbySMEsinJordanwas examined,aresearchgapwasidentified.Thatis,thereisalackofunderstandingoftherelationship among computer self-efficacy, system complexity, system compatibility organizational support, perceivedusefulness,perceivedease-of-use,andtheintentiontoadoptcloudERPsystemsbySMEs inJordan.Moreover,culturefactorsintowhatiscriticaltotheintentiontoadoptcloudERPsystems by SMEs (Soh et al, 2000;Krumbholz & Maiden, 2001;Zhao et al, 2014). That is being said, mostoftheidentifiedstudiesintheliteraturereviewwereconductedincountriesthathavedifferent culturesfromJordan.…”
Section: Rationale Of the Studymentioning
confidence: 99%